“It’s the same world through different eyes”: a CLIL project for EFL young learners. - Korosidou, Eleni; Griva, Eleni (Colombian Applied Linguistics Journal, 2016)
This paper presents the design, implementation, and evaluation of a project entitled “It’s the same world through different eyes,” which was based on the principles of the Content and Language Integrated Learning (CLIL) approach and was piloted with 4th grade primary school students (between 9 and 10 years of age). More specifically, we employed a dual-focused approach, focusing equally on EFL (English as a foreign language) and content development. For the purpose of the project, we designed a mini-syllabus with the stories being at the core of the design. The objectives of the project were to a) develop the students’ receptive and productive skills in EFL), b) develop their sensitivity towards diversity, and c) enhance their citizenship awareness. Students were provided with opportunities to express themselves verbally and nonverbally, and participate in a variety of creative activities in a multimodal teaching context. The findings of project indicated students’ improvement regarding both their receptive and productive skills in the target language, and the development of children’s citizenship awareness, and their sensitivity towards diversity.